BDNF and TrkB–p75^NTR Signaling in Alzheimer’s Disease - Syrlybay, Ayanat (Eurasian Journal of Applied Biotechnology, 2025)
Background: Alzheimer’s disease (AD), the leading cause of dementia, is characterized by synaptic dysfunction, neuronal loss, and cognitive decline. Brain-derived neurotrophic factor (BDNF) regulates hippocampal neurogenesis, synaptic plasticity, and memory. Dysregulation occurs early, already in mild cognitive impairment (MCI), with mBDNF reduced by 30–35% and proBDNF by 20%, correlating with cognitive decline. Mature BDNF activates TrkB to promote neuronal survival and plasticity, while proBDNF binds p75^NTR, triggering apoptosis and synaptic weakening. Amyloid-β accumulation and tau hyperphosphorylation exacerbate this imbalance, downregulating TrkB and upregulating p75^NTR, shifting signaling toward neurodegeneration. Materials and methods: I conducted a structured review (2019–2025) of experimental and clinical studies on BDNF expression, receptor changes, and therapeutic interventions across AD stages, focusing on stage-specific biomarkers, intranasal delivery, and receptor-targeted treatments. Results: Across AD stages, the mBDNF/proBDNF ratio declines progressively. TrkB expression decreases sharply in hippocampal and cortical regions from MCI to AD, preceding neuronal loss, while p75^NTR increases, amplifying amyloid toxicity and synaptic degeneration. Preclinical interventions show that TrkB agonists restore synaptic density and cognition, and p75^NTR blockade prevents dendritic spine loss. Intranasal and exosome-mediated BDNF delivery improves function even after symptom onset. Clinical trials failed mainly due to poor BBB penetration, short BDNF half-life, lack of stage-specific biomarkers, and late treatment initiation. Conclusion: BDNF signaling progressively declines in AD, with early mBDNF/TrkB loss and compensatory p75^NTR upregulation driving neurodegeneration. Interventions are most effective in early stages, while late-stage treatments have limited impact. Early, biomarker-guided targeting of BDNF pathways may offer the best chance to slow disease progression. Keywords: BDNF, TrkB, p75^NTR, Alzheimer’s disease, mild cognitive impairment, neurotrophin. References: Zota, I., Chanoumidou, K., Gravanis, A., Charalampopoulos, I. Stimulating myelin restoration with BDNF: a promising therapeutic approach for Alzheimer’s disease. Front. Cell. Neurosci. 18 (2024). Ginsberg, S.D., Malek-Ahmadi, M.H., Alldred, M.J., Chen, Y., Chen, K., Chao, M.V., Counts, S.E., Mufson, E.J. Brain-derived neurotrophic factor (BDNF) and TrkB hippocampal gene expression are putative predictors of neuritic plaque and neurofibrillary tangle pathology. Neurobiol Dis 132 (2019). Numakawa, T., Kajihara, R. Involvement of brain-derived neurotrophic factor signaling in the pathogenesis of stress-related brain diseases. Front Mol Neurosci 16 (2023). Braschi, C., Capsoni, S., Narducci, R., Poli, A., Sansevero, G., Brandi, R., Maffei, L., Cattaneo, A., Berardi, N. Intranasal delivery of BDNF rescues memory deficits in AD11 mice and reduces brain microgliosis. Aging Clin Exp Res 33, 1223–1238 (2021). Azman, K.F., Zakaria, R. Recent advances on the role of brain-derived neurotrophic factor (BDNF) in neurodegenerative diseases. Int J Mol Sci 23, 6827 (2022). Alqahtani, S.M., Al-Kuraishy, H.M., Al Gareeb, A.I., Albuhadily, A.K., Alexiou, A., Papadakis, M., Hemeda, L.R., Faheem, S.A., El-Saber Batiha, G. Unlocking Alzheimer’s Disease: The Role of BDNF Signaling in Neuropathology and Treatment. Neuromolecular Med 27, 36 (2025). El Ouaamari, Y., Van den Bos, J., Willekens, B., Cools, N., Wens, I. Neurotrophic Factors as Regenerative Therapy for Neurodegenerative Diseases: Current Status, Challenges and Future Perspectives. Int J Mol Sci 24, 3866 (2023).